Work in the Intersections: A Black Feminist Disability Framework - Bailey, Moya; Mobley, Izetta Autumn (Gender & Society, 2019)
A Black feminist disability framework allows for methodological considerations of the intersectional nature of oppression. Our work in this article is twofold: to acknowledge the need to consider disability in Black Studies and race in Disability Studies, and to forward an intersectional framework that considers race, gender, and disability to address the gaps in both Black Studies and Disability Studies. By employing a Black feminist disability framework, scholars of African American and Black Studies, Women’s, Gender, and Sexuality Studies, and Disability Studies have a flexible and useful methodology through which to consider the historical, social, cultural, political, and economic reverberations of disability.
Keywords: EDI; afro-féminisme; approches et analyses; capacitisme; care; cours; discipline; féminisme afroaméricain; histoire et politique; intersectionnalité; philosophie; premier cycle; racisme; ressource en ligne; santé; sciences humaines; sex1920; sexisme; systèmes d'oppressions; thématiques; études critiques du handicap; études de genres

L’inclusion du Black feminism dans la philosophie politique: une approche féministe de la décolonisation des savoirs - Berthelot-Raffard, Agnès (Recherches féministes, 2018)
Fondé sur ce que l’autrice nomme l’« approche féministe de la décolonisation des savoirs », cet article aborde la place du féminisme noir dans la philosophie politique. L’autrice montre que la pensée féministe noire est une philosophie de la justice sociale. À partir de la notion de « modestie épistémique » proposée par Eva Feder Kittay, l’autrice examine comment l’ignorance du système de valeurs et des expériences des femmes noires dans les théories libérales constitue une injustice herméneutique pour les intellectuelles qui édifient le Black feminism comme théorie de la justice raciale et de genre.
Keywords: afro-féminisme; amériques; approches et analyses; belgique; black feminism; canada; care; cours; discipline; europe; europe francophone; france; féminisme décolonial; féminismes noirs; histoire et politique; injustices herméneutiques; justice sociale; philosophie; philosophie politique; pol4212; premier cycle; québec; régions géographiques; sciences humaines; suisse; thématiques; éthique

Se défendre : une philosophie de la violence - Dorlin, Elsa (Zones, 2017)
"En 1685, le Code noir défendait " aux esclaves de porter aucunes armes offensives ni de gros bâtons " sous peine de fouet. Au xixe siècle, en Algérie, l'État colonial français interdisait les armes aux indigènes, tout en accordant aux colons le droit de s'armer. Aujourd'hui, certaines vies comptent si peu que l'on peut tirer dans le dos d'un adolescent tout en prétendant qu'il était agressif, armé et menaçant. Une ligne de partage oppose historiquement les corps " dignes d'être défendus " et ceux qui, désarmés ou rendus indéfendables, sont laissés sans défense. Ce " désarmement " organisé des subalternes et des opprimés au profit d'une minorité jouissant d'un droit permanent à porter des armes et à en user impunément pose directement, pour tout élan de libération, la question du recours à la violence pour sa propre défense. Du jiu-jitsu des suffragettes aux pratiques insurrectionnelles du ghetto de Varsovie, des fusils des Black Panthers aux patrouilles queer, Elsa Dorlin retrace une généalogie philosophique de l'autodéfense politique. Derrière l'histoire officielle de la légitime défense, il est ici question du récit des " éthiques martiales de soi ", ces histoires ensevelies où le Sujet ne préexiste pas à sa propre défense, où le fait de se défendre en attaquant apparaît à la fois comme la condition de possibilité d'un soi et la matière des mythologies politiques. Cette histoire - une histoire de la violence - conditionne la définition même de la subjectivité moderne. Elle s'écrit à la lumière d'une relecture critique de l'histoire de la philosophie politique, où Hobbes et Locke sont à confronter avec Franz Fanon, Michel Foucault ou Judith Butler."--Page 1 et 4 de la couverture.
Keywords: afro-féminisme; approches et analyses; cours; discipline; fem3100; féminisme afroaméricain; féminisme décolonial; féminismes noirs; histoire et politique; mouvements sociaux; philosophie; premier cycle; racisme; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences

Life notations of Daisy Sweeney: Reflections of othermothering, musicianship and Montreal - Campbell, Arlene (Université York, 2012)
The life story of Mrs. Daisy Sweeney, an African Canadian native of Montreal, Quebec, helps fill a void in the historical documentation of Montreal Blacks (especially female elders). Of particular significance is her prominence as a music educator and othermother during her life. The current literature on African Canadian othermothering experiences is not synonymous with both White or African American females and inclusion of their voices in academic, as well as mainstream spaces, is virtually non-existent. This dissertation asks: What did it mean to be a first generation 'Negro' working class bilingual female in a largely hostile White francophone Quebec metropolis in the early 20th Century? How can her narratives help shape and inform life history and African Canadian othermothering research? My sojourn with Mrs. Daisy Sweeney referenced African centered epistemology in my conceptual understanding of herself and community mothering. Capturing her conversations meant engaging with multiple methodologies articulated through African oral traditions, life history, archival canons and interdisciplinary inquiries. It is striking to note that there were not only certain tensions associated with memory loss and physical limitations (prompted by the aging process) that destabilized and enriched our 'interactive' communication, but also revealed a rupture and reversal of the participant/researcher dynamic. In spite of blatant racial discrimination that plagued Montreal's Black communities during that time, Daisy Sweeney fulfilled a life-long dream and taught hundreds of children the canon of classical piano for over 50 years. She lived her voice through her music, finding ways to validate her own identity and empowering others in the process. She used the musical stage as her platform to draw invaluable connections between race, gender, language and social class. Daisy Sweeney's generation of othermothers is dying out and, as the carriers of culture, the urgency to tell their stories must be emphasized. The account respects, reclaims and reflects those voices. It is time to write in African Canadian female elders and diversify the exclusionary genre of life history and archival research.
Keywords: 1900-1999; DIG; afro-féminisme; amériques; approches et analyses; discipline; femmes* noires; histoire et politique; maternité; montréal; musique; mémoires/thèses; philosophie; périodes historiques; québec; racisme; ressource en ligne; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; travail